Salidroside protects renal tubular epithelial cells from hypoxia/reoxygenation injury in vitro - Yan Sun; Liru Xun; Gang Jin; Lei Shi (Elsevier, 2018)
Oxidative stress, inﬂammation and cell apoptosis are important mechanisms of renal ischemia/reperfusion (I/R) injury. Salidroside, a natural phenylpropanoid glycoside, possesses anti-inflammatory, anti-oxidative, and anti-apoptotic effects. However, the effect of salidroside on renal I/R injury has not been fully elucidated. The present study aimed to investigate the effect of salidroside on renal I/R injury in vitro. Our results showed that salidroside improved the viability of human renal tubular epithelial cells (HK-2) in response to hypoxia/reoxygenation (H/R). Salidroside caused apparent decrease in the levels of reactive oxygen species (ROS) and malondiaidehyde (MDA), and significant increase in superoxide dismutase (SOD) activity in HK-2 cells. Pretreatment with salidroside markedly inhibited the production levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-6 in a dose-dependent manner. Salidroside treatment exhibited significant increase in Bcl-2 expressions, and decrease in Bax expressions and caspase-3 activity when compared with the H/R group. Salidroside decreased the levels of toll-like receptor 4 (TLR4) and p-p65 in HK-2 cells. Overexpression of TLR4 significantly attenuated the effects of salidroside on cell viability, oxidative stress, cytokine production and cell apoptosis in HK-2 cells. These findings indicated that salidroside protected HK-2 cells from H/R stimulation, which was mediated by the TLR4/NF-κB pathway. Keywords: Acute kidney injury (AKI), Ischemia/reperfusion (I/R), Hypoxia/reoxygenation (H/R), Salidroside, Oxidative stress, Inﬂammation